KETERAMPILAN ABAD 21 DALAM PEMBELAJARAN - Badjeber, Rafiq; Suciati, Indah; Sartika, Nurhalida (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study is to analyze 21st century skills in learning. The research method used is Systematic Literature Review. Data was collected by documenting and reviewing literature in the National Library of Indonesia and Google Scholar databases related to 21st century skills in learning in the 2020-2021 period as many as 520 literatures. A total of 20 literatures were analyzed using the Miles & Huberman interactive model by collecting data, reducing data using thematic analysis techniques, presenting data, and drawing conclusions. The findings provide insight into the methodology and results of research on 21st century skills, namely 21st century skills that are positively and significantly correlated with perceptions, technology, learning outcomes, and self-efficacy. The use of inquiry learning models, Blended Learning, PBL, and project-based learning are effective in improving 21st century skills